Matrix metalloproteinase Nas15 regulates the lumen formation and expansion in Ciona notochord - Bi, Jianqing; Ge, Yonghang; Wang, Zhuqing; Peng, Hongzhe; Dong, Bo (Frontiers in Ecology and Evolution, 2024)
Lumen formation, as a key process of biological tube construction, is essential in various physiological processes such as nutrient and waste transporting, gas exchanging, and structural supporting. However, the mechanisms underlying tubular lumen development are still not fully understood. In the present study, we identified a matrix metalloproteinase, Nas15, which is enriched in the apical domain of the Ciona embryonic notochord. The expression level of the Nas15 gene significantly increased during notochord lumen formation and expansion. Nas15 loss-of-function resulted in abnormal notochord lumen expansion in Ciona embryos. Besides, yeast two-hybrid screening and CO-IP results indicated a Phosphatase 2 Catalytic Subunit Alpha (PPP2CA) physically interacted with Nas15. PPP2CA also involved in notochord lumen formation via localizing Nas15. Furthermore, we investigated the distribution of laminin in Nas15 disrupted embryos. In conclusion, our results revealed a mechanisms of how notochord cells regulating lumen expansion via metalloproteinase-mediated ECM localization. This findings provide insight into the mechanisms of tubular organ lumen formation and serve as a reference for research on human abnormal lumenogenesis diseases.